ASSESSMENT ON THE LEVEL OF WORKER SATISFACTION ON WELFARE PROVISIONS ON CONSTRUCTION SITES IN GHANA - DOK YEN, DAVID MBABIL; Tabi, K. Nana; Adinyira, E. (Advances in Social Sciences Research Journal, 2018)
Construction worker’s efficiency can increase significantly with satisfactory welfare facilities in the area of adequate toilets, washing facilities, places to eat, and storage place for clothing and so on, and these could be the drivers for high output and increase in profit to a firm where and when they are provided. However, these basic requirements are often inadequate and in worst case are neglected at most construction sites. The aim of this research was to assess the level of worker’s satisfaction on welfare provisions for construction sites in Ghana. The objectives set for the study were to evaluate worker’s satisfaction in construction sites with regards to welfare provisions on site. The population sample for this study consisted of all active construction sites at the Kotoka International Airport (KIA) vicinity. Eighty (89) copies of the questionnaires were administered to permanent workers (the respondents) in five (5) construction sites with on-going construction activities in this study. Structured questionnaire and the census sampling technique were used to collect data. Descriptive statistics was employed to analyze primary data into percentages and frequencies. The study revealed that 69% of construction site workers in Ghana are not satisfied with the level of welfare facilities provided at site by their employers. The researchers discovered that accessibility to welfare facilities, provision of adequate number of welfare facilities, regular maintenance, illumination of space and closeness of welfare facilities were the most influential factors on the level of satisfaction of site workers in the Ghanaian construction industry. The study therefore, recommends that there should be regular assessment and enforcement conducted by policy makers and consultants on the quality of welfare facilities provided by contractors, based on the labour Act regulation on welfare provision on construction sites, to ensure that they are up to standard for workers on site.